(untitled) (Colombia Medica, 2018)
Introduction: Calciphylaxis is an infrequent disease that almost exclusively affects patients with chronic kidney disease, although cases have been observed in patients without renal function impairment. The diagnosis is mainly made by clinical manifestations and subsequently confirmed by radiological and histological study. The optimal treatment is not known, although there is a consensus that a multifactorial approach is required. Clinical Case: A 68-year-old woman on hemodialysis for 2 years, who presented a painful nodular lesion in the left thigh, a skin biopsy was performed resulting in a diagnosis of calciphylaxis. Treatment and Outcome: Treatment was started with intravenous sodium thiosulfate. Pamidronate is added intravenously, three months later, due to an unfavorable evolution. After 6 months of treatment, improvement in nodular lesions and healing of the ulcerated lesion was observed to be generally well tolerated treatment. Conclusion: The combined treatment of sodium thiosulfate, pamidronate and calcitomimetics has been effectiveand safe for the treatment of calciphylaxis, inducing complete remission.